Pengaruh Bauran Pemasaran Terhadap Kepuasan dan Loyalitas Konsumen Minyakita di Kota Pangkalpinang - Viona Widytiya; Eddy Jajang Jaya Atmaja; Muntoro Muntoro (Journal of Integrated Agribusiness, 2024)
This study aims to analyze the effect of the marketing mix, including product, price, place, and promotion, on consumer satisfaction and loyalty among Minyakita buyers at minimarkets, grocery stores, and traditional markets in Pangkalpinang City. Conducted in July-August 2024, this research utilized a survey method with an accidental sampling technique, collecting data from 100 respondents. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS Version 4.0. Findings indicate that price, place, and promotion directly influence satisfaction significantly, while product does not. Product, place, and promotion have a significant effect on loyalty, while price does not. Indirectly, product and price do not significantly affect loyalty through satisfaction, whereas place and promotion do. Satisfaction has a significant impact on loyalty.